SRF: a seriously responsible factor in cardiac development and disease - Deshpande, Anushka; Shetty, Prithviraj; Frey, Norbert; Rangrez, Ashraf Yusuf (Journal of biomedical science, 2022)
The molecular mechanisms that regulate embryogenesis and cardiac development are calibrated by multiple signal transduction pathways within or between different cell lineages via autocrine or paracrine mechanisms of action. The heart is the first functional organ to form during development, which highlights the importance of this organ in later stages of growth. Knowledge of the regulatory mechanisms underlying cardiac development and adult cardiac homeostasis paves the way for discovering therapeutic possibilities for cardiac disease treatment. Serum response factor (SRF) is a major transcription factor that controls both embryonic and adult cardiac development. SRF expression is needed through the duration of development, from the first mesodermal cell in a developing embryo to the last cell damaged by infarction in the myocardium. Precise regulation of SRF expression is critical for mesoderm formation and cardiac crescent formation in the embryo, and altered SRF levels lead to cardiomyopathies in the adult heart, suggesting the vital role played by SRF in cardiac development and disease. This review provides a detailed overview of SRF and its partners in their various functions and discusses the future scope and possible therapeutic potential of SRF in the cardiovascular system.
Gesehen am 15.07.2022